A self-reported cross-sectional study on the oral function and the quality of life in children with stunted growth - Eunike Sianturi; Risti Saptarini Primarti; Arlette Suzy Setiawan (Frontiers Media S.A., 2023)
BackgroundFailure to catch up with growth in toddlerhood will stunt elementary school children, which continues to cognitive decline and oral motor coordination. Verbal motor skills play an essential role in the oral function of the stomatognathic system, which includes mastication, swallowing, and speech. Therefore, early attention to oral function disorders of the stomatognathic system can avoid complications in children's nutritional status and quality of life.ObjectiveThe objective of this study was to analyze the correlation of oral function of the stomatognathic system with Oral Health-Related Quality of Life (OHRQoL) in stunting children.MethodsThis cross-sectional study correlates with 58 children aged 7-12 years with a history of stunting in toddlerhood from the Pasir Jambu District, Bandung Regency. The oral function of the stomatognathic system was evaluated by Adapted Orofacial Myofunctional Assessment Protocol and OHRQoL with Child Oral Health Impact Profile Short Form (COHIP-SF 19).ResultsThe results were statistically analyzed using Spearman's rank correlation and Kendall's coefficient of concordance correlation tests. The results showed that the research subjects had a significant relationship in each variable and the three variables of the oral function of the stomatognathic system (chewing, swallowing, and speech) with OHRQoL with a p-value <0.05. The study concluded that the oral function of the stomatognathic system (chewing, swallowing, and speech) is related to OHRQoL in children with stunted growth.